Pemanfaatan Google Classroom Sebagai Media Pembelajaran Dimasa Pandemi MI NURUL HUDA Sukaraja - Eva Widayanti; Epi Tamala; Pandu Eka Prasetya; Tria Rofiqotutdari (Latifah Pres, 2021)
The Covid-19 pandemic that has hit the world for more than one year has had an impact on changes in teaching and learning activities. This country is no exception, since March 2020 online learning activities have become an option for the ministry of education and culture to prevent the spread of the Covid-19 virus from spreading. The practice of online education (one year online learning) is carried out by various levels of education. There are no longer learning activities in classrooms as is commonly done by teacher educators and lecturers. Today, internet literacy has become a very important role to be developed in our basic life. Therefore, the education sector needs to use information technology in the learning process both in schools and in high schools. Google Classroom is one of the accesses that makes it easier for educators in the learning process. This is the right step, as a result of which many educators are not ready to face this drastic change in teaching methods. Meanwhile, there is practically no other way to minimize the spread of Covid-19 other than by limiting human encounters in large numbers through social distancing measures. The government also limits meetings, to a maximum of 30-40 people. Even then, with very strict health protocols, namely the use of masks, maintaining a minimum distance of 1.5 meters and washing hands with soap. This is based on the opinion of health experts around the world after they conducted research on how to break the Covid-19 chain.